Production of the exopolysaccharide from Lactiplantibacillus plantarum YT013 under different growth conditions: optimum parameters and mathematical analysis - Rentao Zhang; Zhongkun Zhou; Yunhao Ma; Kangjia Du; Mengze Sun; Hao Zhang; Hongyuan Tu; Xinrong Jiang; Juan Lu; Lixue Tu; Yuqing Niu; Peng Chen (International Journal of Food Properties, 2023)
Exopolysaccharides (EPSs) are highly heterogeneous natural polymers, can exhibit some unique bio-logical activities, such as anti-oxidation, inflammation regulation, anticancer and anti-viral activities, etc. A new type of EPS was obtained from the fermentation supernatant of Lactiplantibacillus plantarum YT013. However, the low yield of EPS posed a challenge for further research and application. Therefore, in this study, the production process of EPS was optimized, and anti-cancer cells proliferation activity was investigated. Identified the best single-factor conditions for EPS production, including initial pH 6, inoculation amount 5% (v/v), temperature 37°C, cultivation time 36 h, glucose 3% (w/v), soy peptone 1.5% (w/v), KH2PO4 0.3% (w/v). Under these conditions, the maximum production of EPS reached 0.630 mg/mL, which is 1.31 times higher than that before optimization. Concurrently, the nonlinear model was used for fitting, and it was found that the Voigt nonlinear model was in better agreement with the optimization results, which can be used as an effective tool for optimizing EPS production conditions. Furthermore, the anti-proliferative activity of EPS was evaluated using the human gastric cancer AGS cell line in vitro. MTT assay revealed a strong inhibitory effect of EPS on AGS cell proliferation. Additionally, flow cytometry analysis indicated that EPS promoted apoptosis in AGS cells. Lactiplantibacillus plantarum YT013 EPS, as a biodegradable and nontoxic natural active substance, shows potential as a natural antitumor substance.